Bridging tradition and innovation: a constitution-guided framework for personalized blood pressure management in acute ischemic stroke - Xuran Zhang; Xuran Zhang; Kegang Cao; Li Zhou; Jinxian Liu; Yufeng Ding (Frontiers in Medicine)
BackgroundElevated blood pressure (BP) in acute ischemic stroke (AIS) significantly impacts clinical outcomes, yet optimal BP management remains contentious due to patient heterogeneity. Traditional Chinese medicine (TCM) constitution theory categorizes individuals into distinct physiological patterns, offering a novel framework to address this variability. This study integrates TCM constitutional theory into modern AIS care to propose a personalized BP management ‌hypothesis.MethodsA systematic review and meta-analysis were conducted across nine databases, including PubMed, Web of Science, Scopus, the Cochrane Library, ScienceDirect, the Chinese National Knowledge Infrastructure, Wanfang Data, VIP Database, and China Biology Medicine, covering publications up to January 2025. We analyzed TCM constitution distributions in AIS, hypertension, hypotension, AIS with hypertension, ischemic stroke (IS) with hypertension, and ischemic cerebrovascular disease with hypoperfusion, correlating constitutional types with clinical outcomes. We employed the Agency for Healthcare Research and Quality (AHRQ) checklist to evaluate the methodological quality of cross-sectional studies and utilized the Newcastle-Ottawa Scale (NOS) for quality assessment of cohort and case–control studies. Subgroup and sensitivity analyses were performed, and publication bias was assessed. A constitution-guided framework for BP management was developed through evidence synthesis.ResultsFifty-four studies were included in the study, with the majority being of moderate-to-high quality. The findings demonstrated that Phlegm-dampness, Qi-deficiency, Yin-deficiency, and Blood-stasis constitutions predominated in AIS patients with hypertension. Subgroup and sensitivity analyses confirmed the robustness of the results. Most analyses demonstrated no evidence of publication bias. Although several analyses indicated potential publication bias, the primary conclusions withstood the trim-and-fill adjustment and remained robust. A TCM constitution-based BP management hypothesis was proposed: patients with Phlegm-dampness or Blood-stasis constitutions may benefit from intensive BP control, whereas Qi-deficiency and Yin-deficiency types may require conservative strategies to mitigate hypoperfusion risks.ConclusionThis integration of TCM constitutional theory into AIS BP management provides a potential framework for advancing precision care to improve clinical outcomes in AIS patients. Further validation in multicenter cohorts and mechanistic exploration is warranted to enhance clinical applicability (Registration information: https://www.crd.york.ac.uk/PROSPERO2/view/CRD420250655689).